Unveiling the antiglioblastoma potential of harmicens, harmine and ferrocene hybrids - Poje Goran; Šakić Davor; Marinović Marina; You Jiangyang; Tarpley Michael; Williams Kevin P.; Golub Nikolina; Dernovšek Jaka; Tomašič Tihomir; Bešić Erim; Rajić Zrinka (Acta Pharmaceutica)
The poor prognosis of glioblastoma multiforme, inadequate treatment options, and growing drug resistance urge the need to find new effective agents. Due to the significant anti-cancer potential of harmicens, hybrid compounds which comprise harmine/β-carboline and ferrocene moiety, we investigated their antiglioblastoma potential in vitro and mechanism of action (inhibition of DYRK1A, Hsp90, anti-oxidative activity). The results have shown that triazole-type harmicens, namely 5, with a ferrocene moiety in C-3 position of the β-carboline ring (IC50 = 3.7 ± 0.1 µmol L–1, SI = 12.6) and ., the C-6 substituted harmicene (IC50 = 7.4 ± 0.5 µmol L–1, SI = 5.8) exert remarkable activity and selectivity against human malignant glioblastoma cell line (U251) in vitro. On the other hand, amide-type harmicens 10, 12, and 14 exhibited strong, but non-selective activity, in the low micro-molar range. Mechanistic studies revealed that among active compounds, amide-type harmicens 12 and 14 inhibit DYRK1A and Hsp90 CTD, whereas compound 14 showed pronounced antioxidative activity. Therefore, the antiproliferative activity of harmicens might be a combination of complex molecular interactions.